Une analyse d’une production de discours rapporté : l’introduction des tours de parole dans “Hills Like White Elephants” d’Ernest Hemingway - Grégoire LACAZE (E-REA)
Hemingway’s short story, “Hills Like White Elephants”, is largely built around a reported dialogue involving two main characters. Although many critical studies have been devoted to this short story, focusing especially on Hemingway’s style, this paper seeks to explore a relatively neglected theme, namely the introduction of direct speech, which acquires significant importance in the reception of the short story.Thanks to the dialogue that materializes as an occurrence of reported speech produced by a reporter, we will study how the narrator chooses to introduce the various turns constituting the dialogue. This analysis, inscribed within the framework of an enunciative approach, aims at pointing out the stylistic devices used by the author. Both linguistic and semantic aspects will be taken into account as well as the specificities induced by the genre of the short story and their influence on the stylistic choices made by the author. The analysis will be backed up with statistical data related to the composition of the various structures introducing the characters’ words.